PENGUJIAN PERATURAN PERUNDANG-UNDANGAN DI BAWAH UNDANG-UNDANG OLEH MAHKAMAH AGUNG - Sudarsono Sudarsono (MIMBAR YUSTITIA, 2017)
In realizing unity in the legislation system in Indonesia, it is known that there is a Judicial Review conducted by the Constitutional Court and the Supreme Court. Article 9 of Law Number 12 Year 2011 concerning the establishment of laws and regulations states that the Constitutional Court has the authority to examine the legality of a law with the test stone of the 1945 Constitution of the State of the Republic of Indonesia, while the Supreme Court has the authority to examine the legality of a legislation under the law with a test stone legislation. The Supreme Court in exercising its authority has issued the Supreme Court Regulation No. 1 of 2011 on the Right to Material Test. In its development, the Supreme Court Regulation Number 1 Year 2011 needs to be refined, whether related to the definition of "laws and regulations" that become the competence of the Supreme Court, as well as the improvement of procedural law such as grace period of submission of answers, type of verdict, to the involvement of the parties in litigation a dispute on the Right to Material Test in the Supreme Court. The legal issues in this study are: (1) Competence of the Supreme Court in conducting examination of the petition for Material Test Rights; and (2) Procedural Law in the examination of the petition for Judicial Review of Judicial Rights by the Supreme Court. This research is legal research, with approach of statute approach and conceptual approach. From this study it is found that: (1) the definition of "legislation" which can be tested in the Supreme Court based on Supreme Court Regulation Number 1 Year 2011 is very open (open texture) and different from the definition of "legislation as Article 1 Number 2 of Law Number 12 Year 2011; and (2) in relation to the procedural law at the examination of the Material Rights Trial in the Supreme Court, it is known that the grace period of the response of only 14 (fourteen) days, the inappropriate "unlawful" decision, the involvement of the parties only submission of requests and answers only, to the model of execution of decisions that are not in accordance with the character of the test of a norm of legislation. From both of these things, it is necessary to improve the Supreme Court Regulation Number 1 Year 2011.